The Dual Role of Wives in Modern Households to Improve Family Welfare: An Analysis of Maqashid Shari'ah in the Livelihood Status of Working Wives - Sayyidun Najib (Rechtsvinding, 2026)
The fact that the number of wives who work outside the home in terms of modern households or containers raises critical questions about the livelihood status of wives who work under Islamic law. In salaf fiqh, the obligation to provide for the husband is entirely on the shoulders of the husband as the head of the family, regardless of the economic condition of the wife. However, social change requires repeating the discussion in accordance with the current modern conditions. This article aims to analyze the status of the law on providing for workers' wives through the maqaṣhid shariaʿah approach, in order to understand the significance and flexibility of Islamic law to address a modern challenge today. This research is a concept of library research, it can also be called a literature study that uses a qualitative research approach and the data centers used are books and books of salaf and contemporary fiqh (modere) as well as scientific journals. The results of the study show that the basic principle and obligation to provide for the husband to his wife still applies, while maqaṣid shari'ah allows for a form of adjustment based on the principles of tarad'hi (mutual will), benefit, mutual mercy and justice. Thus, the wife's involvement in the family economy does not necessarily disappear or eliminate the right to the wife's maintenance, before there is an explicit agreement and replaces the responsibility. This study suggests the importance of a maqa ṣ hid-based family guidanceto ensure the harmony of Muslim household relations in this modern era.